Somewhere over the rainbow ‐ third sector research in and beyond coronavirus. (1st July 2020) - Macmillan, Rob
Abstract : The coronavirus pandemic has rapidly become a multifaceted global crisis, disrupting economies, livelihoods and ways of life, with significant ramifications for the third sector. This paper seeks to prompt a conversation about third sector research agendas, which might be animated in and beyond coronavirus, focusing primarily on the experience of the sector in the UK but including references globally. After a brief discussion of the acute three-dimensional crisis facing the sector, the paper raises questions for now and later at three interconnected levels: of practice, organisation and society. The paper concludes with a call for critically engaged curiosity about the role and fortunes of the third sector in a time of lockdown and its aftermath.